Competitividade brasileira e o papel do governo frente a pesquisa e desenvolvimento : análise do perfil das empresas inovadoras do país e o posicionamento do governo - Silva, Luiz Alberto Vasconcelos (2022)
This study investigates whether financial stimuli present in government programs for R&D are helping companies to become more competitive, focusing on “Lei do Bem”, Act nº 11.196/2005. The argument is that normally Brazilian companies face difficulties to create innovation, either due to difficulties in financing their activities, lack of knowledge about possibilities or systemic obstacles. The research is carried out quantitatively method through multiple regression and is based on documental analysis of reports and databases from the IBGE, World Economic Forum, the Investor Relations Website of the companies in [B]³ and the Economatica® database. As a result, the research observed that government subsidies contribute to the country's competitiveness, nevertheless, the government's role in providing subsidies for RD&I in companies has not been relevant to increase Brazilian competitiveness compared to neighboring countries due to subsidies programs premises, RD&I is an activity that indicates higher market value for the companies in the sample and the profile of the company that uses the Law of Good benefit differs from the profile of the vast majority of Brazilian companies.